Going-Concern Audit Report: The Role of Audit Committee - Suhaimi Ishak (International Journal of Economics and Financial Issues, 2016)
The objective of the study is to discuss the roles of audit committee (AC) towards the going-concern audit report issued by the external auditor. Based on the International Standard on Auditing that governing the auditors' works and findings from previous studies, clearly the auditor has the responsibility on the company's going-concern issues. The existence of AC as the board committee together with its strong composition seen to be a good measure to monitor the issues of going-concern that pertaining to the company's viability in future. The responsibility on this issue to AC is parallel with the guidelines in corporate governance codes as practised by most countries in the world.